Postoperative dizziness after cochlear implant surgery: can it be caused by air? - Ketterer, Manuel Christoph; Everad, Friederike; Lützen, Niklas; Rauch, Ann-Kathrin; Aschendorff, Antje; Arndt, Susan; Jakob, Till F. (Frontiers in Neurology, 2024)
ObjectivesMultiple studies have described the onset and variable incidence of postoperative acute vertigo following cochlear implant (CI) surgery. However, postoperative imaging has not yet been specifically evaluated with special focus on vertigo. The aim of this study is to assess the incidence and causes of new-onset, acute postoperative vertigo following CI surgery using cone beam computed tomography (CBCT).Materials and methodsThis is a retrospective study involving ten patients who experienced postoperative dizziness and ten matched controls without dizziness. All patients received a cochlear implant (CI) between 2020 and 2024. The matching analysis was performed based on the implant, electrode array, and access to the cochlear. We analyzed the postoperative CBCT scans for changes suspicious of air trapping, a so-called pneumolabyrinth in the vestibule using minimal Hounsfield Units (HU).ResultsWe compared postoperative CBCT images for electrode array position monitoring in ten patients with vertigo versus ten patients without vertigo after CI surgery. Among the ten patients with postoperative dizziness, six showed suspicious changes in the vestibule consistent with the presence of air. These air-related changes were observed in the vestibule and, in one patient, additionally in the horizontal semicircular canal. Minimal HU were significantly different and confirmed the suspicion of intravestibular air.ConclusionThis is the first study to describe the suspicion of intravestibular air in CI patients with postoperative vertigo. Therefore, suctioning after the fenestration of the round window membrane or the endosteum after cochleostomy, as well as actions such as bending, pressing, and nose-blowing by the patient, should be strictly avoided. Furthermore, this finding highlights the importance of carefully sealing the electrode array at the cochleostomy site with connective tissue. Risk factors for the development of a pneumolabyrinth with air in the vestibule include intralabyrinthine or intracranial pressure changes, large cochleostomies or a second cochleostomy and electrode placement in the scala tympani.